Platelet‐derived transforming growth factor‐β1 promotes keratinocyte proliferation in cutaneous wound healing. (5th March 2020) - Chong, Deborah L.W.; Trinder, Sarah; Labelle, Myriam; Rodriguez‐Justo, Manuel; Hughes, Sian; Holmes, Alan M.; Scotton, Chris J.; Porter, Joanna C.
Abstract: Platelets are a recognised potent source of transforming growth factor‐β1 (TGFβ1), a cytokine known to promote wound healing and regeneration by stimulating dermal fibroblast proliferation and extracellular matrix deposition. Platelet lysate has been advocated as a novel personalised therapeutic to treat persistent wounds, although the precise platelet‐derived growth factors responsible for these beneficial effects have not been fully elucidated. The aim of this study was to investigate the specific role of platelet‐derived TGFβ1 in cutaneous wound healing. Using a transgenic mouse with a targeted deletion of TGFβ1 in megakaryocytes and platelets (TGFβ1 fl/fl .PF4‐Cre), we show for the first time that platelet‐derived TGFβ1 contributes to epidermal and dermal thickening and cellular turnover after excisional skin wounding. In vitro studies demonstrate that human dermal fibroblasts stimulated with platelet lysate containing high levels of platelet‐derived TGFβ1 did not exhibit enhanced collagen deposition or proliferation, suggesting that platelet‐derived TGFβ1 is not a key promoter of these wound healing processes. Interestingly, human keratinocytes displayed enhanced TGFβ1‐driven proliferation in response to platelet lysate, reminiscent of our in vivo findings. In summary, our novel findings define and emphasise an important role of platelet‐derived TGFβ1 in epidermal remodelling and regeneration processes during cutaneous wound healing.